Critical literacy and its impact on Black boys' reading readiness - Robinson, Shawn Anthony; Ellis, Antonio L. (Emerald Publishing Limited : Information Age Publishing, Inc., 2023)
"Academic success for African American boys' in Special Education is frequently elusive as the United States continues to endure the legacy of academic discrimination (Blanchett, 2010; Skiba et al., 2008). Consequently, educational policies have not fully protected the equal rights or adequately responded to the learning needs of students' academic shortcomings or taken advantage of their strengths (Parkinson & Rowan, 2008; Tatum, 2005). This persistent reading gap has not closed in generations, which is deeply harmful to our American democracy (Wolf, 2019). With every passing year that goes by without alleviating problems affecting the reading gap, the damage is costly, and no failure is more expensive than the failure to educate African American males in the PK-12 pipeline (Robinson & Thompson 2019). The danger to our students becomes more critical each year, and these are problems that are deeply rooted in America. And, while teachers cannot change the past, we can, and must, change the special education system that shapes the future of students. Thus, a reader's identity becomes shaped by the intersection of factors that are both inherent and neurologically based, and factors that arise as a result of one's home and academic environment (Hoyles & Hoyles, 2010; Robinson, Ford, Ellis, & Hartlep, 2016; Wolf, 2007). Reading instruction must be culturally relevant which can strengthen the reader's identity and capacity for critical thinking (Arya & Feathers, 2012; Flowers, 2007; Robinson, 2017). Critical literacy is grounded in the sociocultural perspective and way of thinking about curriculum, literacies, and honoring students' lived experiences, especially within the contexts of Special Education (Brooks, 2006; Gay, 2002; Norman, 2011). This edited book will fill a needed gap in scholarly research, as manuscripts adopts a critical analysis that brings together the latest theoretical, conceptual, quantitative, qualitative, and mixed methods research studies. Chapters will have clear and explicit implications for educational practice and make a significant contribution to the field of special education and reading instruction"--